Comparing the uses of BIM in the AEC industry with the university curriculum and identifying obstacles to its application - الخير ابراهيم; لما سعود; جمال عمران (Latakia University Journal -Engineering Sciences Series, 2023)
The construction industry is witnessing rapid development in various fields from a technical and technological standpoint. It has become necessary to move away from traditional manual methods and rely on modern digital modeling, which has made engineering colleges seek to achieve a balance between educational curricula and the requirements of the new labor market through continuous development of their programs and learning outcomes. To provide new graduates with the scientific and practical skills necessary to face these changes. This paper aims to identify the uses of BIM and the most common software in the construction industry in Syria, in addition to identifying the most important obstacles facing the application of this methodology in both the construction industry and university curricula. A questionnaire was developed directed to a group of engineering companies, and another questionnaire was directed to Professors and engineers at the Faculty of Civil Engineering at Tishreen University. The results of the analysis of the first questionnaire showed that the most common uses are: architectural modeling, structural modeling and quantity extraction, and the most commonly used software are: AutoCAD and then Architectural Revit. The most important obstacles affecting the application of BIM in the construction industry in Syria are: lack of knowledge of the BIM methodology, lack of desire in change, and not integrating BIM into educational institutions. While the results of the analysis of the second questionnaire, using the risk ranking index, by determining the impact of the obstacle and the possibility of solving it, showed that the three most important obstacles are: the lack of laboratories that can fit all students, the lack of technological equipment, and the lack of different specializations. It was found that most of the departments of the College of Civil Engineering are still in the early stage of introducing BIM within the courses, while there is reliance on the use of this methodology in graduation projects in the Departments of Structural Engineering and Construction Engineering and Management..